Analysis of Survival Aspect Faced by The Main Character in The Revenant's Movie - Jimmi; Khairunas, Sayyid; Yulianto, Krismunandar (JL3T (Journal of Linguistics, Literature and Language Teaching), 2022)
The objective of this paper is to figure out the main character's survival in the wild and to depict what types of survival aspect that the main character used to survive against the enemies. The researchers use a qualitative descriptive research method. It means the technique of collecting data or theories from books and journals obtained from electronic portals and analyzing important notes that have been made. Documentation technique is using to collect whole the data which is appeared in the movie and descriptive analysisis usingto analyze the data have been found. The source of data from this research is The Revenant movie. The researcher uses the theory of DwiYuni who described types of survival and the theory of Sun Tzu in Rikawati that described the strategic of survival. The results showed that(1) 4 types of survival the researcher found in this movie; jungle survival, sea survival, dessert survival, and Antarctic survival.(2) The strategic of survival used by main character: planning, raid tactics, power, moving, and strategies position.